Muslims in Britain: questioning Islamic and national identity - Nur Fuad, Ai Fatimah (Indonesian Journal of Islam and Muslim Societies, 2012)
Islamic identity has been a central issue since the emergence of Islam in theseventh century. Muslims have been interacted with many symbols of religiousidentity since this early time of Islam. Every generation of Muslims has their ownway to show their religious identity. Muslims in Britain are also still continuing tosearch for religious identity. They seek to re-evaluate their identity and constructa sense of what it means to be a Muslim in Britain today. This article would like toelaborate several discussions on Muslimsâ identities in Britain. There are twodifferent opinions on this issue. The first opinion comes from Muslims who believethat a Muslim individual should choose to be either a Muslim or a British.They argue that national values differ from religious norms. The second, however,states that one Muslim can be both a Muslim and a British at the same time.For them, there is no contradiction between being a Muslim and being a Britishcitizen. They argue that nationality and faith can be combined in Muslim individualswho live in Britain.Identitas keIslaman telah menjadi isu utama sejak awal kemunculan Islam padaawal ketujuh Masehi. Sejak awal, Muslim sudah berinteraksi dengan berbagaisymbol identitas keagamaan. Setiap generasi Muslim memiliki cara tersendiriuntuk menunjukkan identitas kegamaan mereka. Begitu juga dengan generasiÂ Muslim saat ini di Inggris, mereka masih mencari identitas keagamaan mereka.Mereka berusaha mengevaluasi kembali dan mencari makna bagaimana menjadiMuslim di Inggris. Artikel ini ingin mengelaborasi beberapa diskusi mengenaiidentitas Muslim di Inggris. Terdapat dua perbedaan pandangan terkait hal ini.Pendapat pertama datang dari Muslim yang percaya bahwa seorang Muslim harusmemilih menjadi Muslim atau seorang warga Inggris. Mereka berpendapat bahwanilai-nilai nasional Inggris berbeda dari norma-norma agama. Namun yang kedua,menyatakan bahwa seorang Muslim bisa menjadi Muslim Inggris pada waktubersamaan. Bagi mereka, tidak ada perbedaan untuk menjadi Muslim atau menjadiwarga Negara Inggris. Mereka berpendapat bahwa keimanan dan nasionalismebisa disatukan dalam diri seorang Muslim yang tinggal di Inggris.